Development of Project-Based Student Work Sheets (LKPD) Based on Biotechnology Materials - Hijrah, Hijrah; Syamsiah, Syamsiah; Junda, Muhammad (Universitas Negeri Makassar, 2023)
This study aims to produce Student Worksheets (LKPD) BasedProject Based Learning (PjBL) Biotechnology materials that are valid and practical. This type of research is research and development (R&D). The development of this LKPD refers to the ADDIE model. The ADDIE stages consist of Analysis, Design, Development, Implementation, and Evaluation. The research instrument was validated by two expert validators. LKPD was validated in two stages. Results The percentage of stage is 78.5% in the valid category. The results of the second stage percentage, namely 88.2%, are in the very valid category. The results of the teacher response questionnaire analysis were 85.28% in the very practical category and thestudent response questionnaire results obtained a value of 81.15% in the very practical category. Based on these results it can be concluded that thedevelopment of Student Worksheets (LKPD) is BasedProject Based Learning (PjBL) Biotechnology material is valid and practical to use in thelearning process. Key words: Biotechnology, Validity, Practical, LKPD, PjBL